2013
DOI: 10.1186/1744-9081-9-41
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between bruxism and orofacial-dystonia? A trigeminal electrophysiological approach in a case report of pineal cavernoma

Abstract: BackgroundIn some clinical cases, bruxism may be correlated to central nervous system hyperexcitability, suggesting that bruxism may represent a subclinical form of dystonia. To examine this hypothesis, we performed an electrophysiological evaluation of the excitability of the trigeminal nervous system in a patient affected by pineal cavernoma with pain symptoms in the orofacial region and pronounced bruxism.MethodsElectrophysiological studies included bilateral electrical transcranial stimulation of the trige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…These data indicate that the inhibitory circuits that innervate trigeminal motoneurons are less excitable in SB patients . However, in a case report in which the patient was affected by pineal cavernoma and pronounced bruxism, the author indicated that bruxism and central oro‐facial pain can coexist but represent 2 independent symptoms . The interneural sensitisation observed during the recovery cycle of MIR might be linked to a combination of the excitatory effect of glutamate and the disinhibition of the inhibitory process that results from the effects of glycine and GABA .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These data indicate that the inhibitory circuits that innervate trigeminal motoneurons are less excitable in SB patients . However, in a case report in which the patient was affected by pineal cavernoma and pronounced bruxism, the author indicated that bruxism and central oro‐facial pain can coexist but represent 2 independent symptoms . The interneural sensitisation observed during the recovery cycle of MIR might be linked to a combination of the excitatory effect of glutamate and the disinhibition of the inhibitory process that results from the effects of glycine and GABA .…”
Section: Discussionmentioning
confidence: 98%
“…However, in a case report in which the patient was affected by pineal cavernoma and pronounced bruxism, the author indicated that bruxism and central oro‐facial pain can coexist but represent 2 independent symptoms . The interneural sensitisation observed during the recovery cycle of MIR might be linked to a combination of the excitatory effect of glutamate and the disinhibition of the inhibitory process that results from the effects of glycine and GABA . Finally, the observed alterations could increase the firing probability of trigeminal motoneurons during sleep, resulting in RMMA.…”
Section: Discussionmentioning
confidence: 99%
“…Dystonia is a movement disorder leading to similar damage in tooth hard tissues as that caused by bruxism. Dystonia is a disorder of involuntary, repetitive, predominantly sustained (tonic), or spasmodic (rapid or clonic resembling myoclonus) muscle contractions [17]. Dystonia may affect almost all striated muscle groups in different body regions.…”
Section: Dystoniamentioning
confidence: 99%
“…It should also be noted that in a very small proportion of OP patients visited by dental specialists, some neurological diseases as intracranial cancers, multiple sclerosis and so on are the underlying symptomatological cause of TMD or OP. These patients, who actually suffer from misunderstood neurological symptoms, may undergo unnecessary dental interventions before the correct diagnosis is made, often too late [7,8].…”
Section: Introductionmentioning
confidence: 99%